Impact of the COVID-19 Pandemic on Medical Students and Students' Perspectives on COVID-19 Policies and Social Media in 2021 and 2022 - Ghazal Becker; Emily K. Ranta; Riddhi S. Shah; Victoria Reyes; H. Dean Sutphin; Alexis M. Stoner (University Library System, University of Pittsburgh, 2023)
Background: The COVID-19 pandemic affected medical students in several ways in 2021 and 2022. In continuation of a previous study, this study sought to determine how the changing nature of the pandemic affected medical students' knowledge, experiences, perspectives on the policies and resources in 2022 compared to 2021. Methods: A qualitative study was conducted via open-ended journaling in 2021 and 2022. Participants were recruited from medical students in the U.S. as well as in Central America and the Caribbean, who were enrolled in a "Global Seminar for Health and Environment". Results: A total of 142 and 72 responses were obtained in 2021 and 2022 respectively. Regarding the COVID-19 policies, U.S. students were thankful for vaccinations and approved of initiatives in their regions in 2021. Later, they were equally divided regarding region-specific pandemic policies. International students mainly approved of the policies in both years. Students consistently noted negative mental health impacts and difficulty with social limitations. U.S. students noted decreased academic opportunities in both years while international students noted family concerns in 2021. U.S. students held negative views about social media due to fearmongering in 2021 and politicization in 2022. International students held neutral and/or positive views about social media. U.S. students relied on the CDC as a source of information while international students utilized the WHO. Conclusion: U.S. students had a more negative outlook as the pandemic progressed. It is difficult to draw comparisons within the international cohort due to limited responses obtained in 2022